2022
DOI: 10.3390/antibiotics11010117
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cephalosporin Treatment on the Microbiota and Antibiotic Resistance Genes in Feces of Dairy Cows with Clinical Mastitis

Abstract: Antibiotics are frequently used to treat dairy cows with mastitis. However, the potential effects of β-lactam antibiotics, such as cephalosporins, on the fecal microbiome is unknown. The objective was to investigate the effects of ceftiofur and cefquinome on the fecal microbiota and antibiotic resistance genes of dairy cows with mastitis. The fecal samples were collected from 8 dairy cows at the following periods: the start day (Day 0), medication (Days 1, 2, and 3), withdrawal (Days 4, 6, 7, and 8), and recov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 39 publications
4
7
0
Order By: Relevance
“…We observed that the microbiome diversity of treated cattle was significantly disturbed in the short term, increasing ARGs conferring resistance to tetracyclines compared to control animals without exposure to OTC. This finding is consistent with previous studies that reported the perturbation of the gut microbiome following antibiotic treatment within a few days after antibiotic exposure [ 25 , 26 , 27 ].…”
Section: Discussionsupporting
confidence: 93%
“…We observed that the microbiome diversity of treated cattle was significantly disturbed in the short term, increasing ARGs conferring resistance to tetracyclines compared to control animals without exposure to OTC. This finding is consistent with previous studies that reported the perturbation of the gut microbiome following antibiotic treatment within a few days after antibiotic exposure [ 25 , 26 , 27 ].…”
Section: Discussionsupporting
confidence: 93%
“…The Bacteroidia and Clostridia dominated the bacterial classes, regardless of the period of time. This is consistent with studies by Kim et al [52], Pajarillo et al [53] and Dong et al [54]. The decreased abundance of Bacilli and Clostridia in the guts of mosaic-tailed rats during the period of illness and treatment with antibiotics is likely reflective of the negative state of the animals at the time.…”
Section: Plos Onesupporting
confidence: 91%
“…So far, the increase in relative numbers of Bacteroides and the decrease in relative numbers of Clostridium in the gut microbiome of pigs after ceftiofur treatment has not been described before. One study did report these changes in the microbiota of dairy cattle after intramuscular ceftiofur administration of 2 mg•kg −1 body weight [64]. Interestingly, the relative abundance of Faecalibacterium increased after treatment (original p-value = 0.01563, q-value = 0.03908).…”
Section: Impact Of Ceftiofur On the Gut Microbiome Of Pigsmentioning
confidence: 99%